Management of Islamic Education Institutions in the Tahfiẓ Al-Quran Program at Ma'had Umar Bin Al-Khattab University of Muhammadiyah Surabaya - Achbar Safrudin (International Consortium of Education and Culture Research Studies, 2021)
Management of Islamic education institutions can be defined as a form of cooperation to carry out planning functions, organizing, preparation of personnel or staffing, direction and leadership, and supervision of the efforts of members of Islamic education institutions and the use of human, financial, physical and other resources by making Islam the foundation and guide in their operational practices to achieve the objectives of Islamic education institutions in various types and forms which essentially try to help someone or a group of students in instilling teachings and / or develop Islamic values. This study wanted to find out the management and defense owned by Islamic education institutions in managing Islamic education institutions. This study aims to determine the management and challenges of Islamic education institutions in the tahfiẓ al- Qur'an program in Ma’had Umar Bin Al-Khattab, Muhammadiyah University of Surabaya. This type of research is qualitative research, namely research that produces descriptive data, namely a type of research that seeks to present data and actual facts about the management of Islamic education institutions in the tahfiẓ al-Qur'an program in Ma'had Umar Bin Al-Khattab University Muhammadiyah Surabaya. Data collection techniques used in this study were (1) interview (2) observation (3) documentation. For data analysis using descriptive techniques, the application is carried out in three activities, namely data reduction, data presentation, and conclusion or verification. The results of this study indicate that first, planning in Ma'had Tahfiẓ Umar Bin Al-Khattab Surabaya carried out activities (1) developing a strategic plan, which included vision and mission, objectives, strategic programs, implementation strategies, monitoring and evaluation; (2) arranging the rules of the santri (3) compiling technical guidelines for the implementation of activities. Second, organizing in managing Ma'had Tahfiẓ Umar Bin Al-Khattab, including (1) arranging the organizational structure and the map of the program's responsibility (2) preparing the tasks and positions of each personnel (3) structuring the program. Third, the mobilization in Ma'had Tahfiẓ Umar Bin Al- Khattab was said to be (1) motivating; (2) coordination; (3) leadership and (4) maintaining good relations with ustadh, santri and staff. Fourth, controlling in Ma'had Tahfiẓ Umar Bin Al-Khattab is divided into (1) monitoring and evaluation (2) assessment. Fifth, the constraints of management of Islamic education institutions in the Islamic program in Ma'ad Umar Bin Al-Khattab consist of, (1) financial activities and operations in Ma'had Tahfiad Umar Bin Al-Khattab Surabaya still rely on permanent donors; (2) makeshift facilities; (3) Inadequate human resources. The six obstacles faced in the tahfiẓ al-Qur'an program are (1) the saturation and laziness felt by the santri in carrying out established programs; (2) guarding the memorization of the Qur'an that has been memorized (3) guarding themselves from immorality. From the results of this study it can be suggested (1) in improving the quality of Islamic education institutions, Ma'had Tahfiẓ Umar Bin Al-Khattab Surabaya should improve the quality of institutional management; (2) The Asia Muslim Charity Foundation (AMCF) should provide funds for operational and learning activities that exist in Ma’had Tahfiẓ Umar Bin Al-Khattab Surabaya; (3) The Asia Muslim Charity Foundation (AMCF) and the Muhammadiyah Union pay more attention to existing facilities in Ma’had Tahfiẓ Umar Bin Al-Khattab Surabaya. (4) the results of this study can be used as reference material in developing and implementing management of educational institutions, especially in Islamic education institutions that implement the tahfiẓ al-Qur'an program; (5) the need for development research on the comparison of management of Islamic education institutions in the tahfiẓ al-Qur'an program, especially the management of educational institutions in Ma’had Tahfiẓ Umar Bin Al-Khattab Surabaya.